Practical test design : selection of traditional and automated test design techniques - Forgács, István; Kovács, Attila (BCS, 2019)
This book presents the key test design techniques, in line with ISTQB, and explains when and how to use them, including in combination, with practical, real-life examples. Automated test design methods are also explored. Tips and exercises are included throughout the book, allowing you to test your knowledge as you progress.